Reassessing Regional Integration in the West Africa Sub-Region: Ecowas’s Prospects and Challenges - Augustus Olukayode Fisher; Soboyejo Akintayo Oludemi (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
This paper attempts a reassessment of the workings and issues attached with ECOWAS in West Africa. There were actually 15 nations in West Africa before ECOWAS was formed, and the region was characterised by the many colonial experiences and administrations that had shaped these states that made up the region. This history also contains a wide range of administrative and bureaucratic traditions, which make it difficult to collaborate, collaborate, and establish institutions. Porous national boundaries make it easier for people to travel about in search of better economic opportunities, as well as for food and small weapons to be transported across borders informally. Francophone, Anglophone, and Lusophone divides continue to influence integration in numerous ways. Disparities in race, language, and religion make it difficult for post-colonial elites to unite people behind a shared national purpose, much alone one with a regional focus. Employing both historical and theoretical methods, this study examines the good and bad of Ecowas in line with the existing efforts among member states. Keywords: